Outcome following second allogeneic hematopoietic cell transplantation: A single‐center experience. (11th January 2018) - Aljasem, Hassan A.; Messner, Hans A.; Lipton, Jeffrey H.; Kim, Dennis Dong Hwan; Viswabandya, Auro; Thyagu, Santhosh; Deotare, Uday; Michelis, Fotios V.
Abstract: Objective: Second allogeneic hematopoietic cell transplantation (HCT) may be indicated following relapse or graft failure following first HCT. Our retrospective single‐center study sought to investigate parameters that influence post‐second allogeneic HCT survival. Method: We investigated 92 patients who underwent second allogeneic HCT between 1980 and 2016 for relapse or graft failure following first HCT. Median age at second HCT was 41 years (range 16‐68), performed for relapse in 59 patients (64%) and for graft failure in 33 patients (36%). Results: On univariate analysis, 3‐year OS of the entire cohort was 35% (95% CI=25‐45). Eastern Cooperative Oncology Group (ECOG) score (3‐year OS 48% for ECOG 0‐1, 18% for ECOG 2‐3, P =.0006), second HCT indication (3‐year OS 43% for relapse, 20% for graft failure, P =.02), time from first HCT to relapse/graft failure (3‐year OS for <12months 21%, for ≥12months 46%, P =.009), and conditioning intensity (3‐year OS for MA 42% vs other regimens 23%, P =.08) significantly influenced OS. Multivariable analysis confirmed ECOG score (HR=2.15 for ECOG 2‐3, 95% CI=1.32‐3.51, P =.002) and second HCT indication (HR=1.67 for graft failure, 95% CI=1.02‐2.75, P =.04) to independently influence survival. Conclusion: Second HCT may offer long‐term survival particularly to patients with good performance status who relapse post‐first HCT.